2000
DOI: 10.1007/bf03030417
|View full text |Cite
|
Sign up to set email alerts
|

Action of malformin A1 on gravitropic curvature in primary roots of maize (Zea mays L.)

Abstract: Malformins, a small family of cyclic pentapeptides, are active plant growth regulators isolated from the fungus Aspergillus niger. We purified malformin A1 from the crude malformin A mixture, and studied its action in the gravitropic response of maize roots. Intact primary roots that had been pretreated vertically with malformin A1 were placed in a humidified box in the horizontal position. Positive curvature (downward) was inhibited in the pretreated roots compared with the control. In addition, we measured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Lee et al [7] suggested that ethylene may modify positive curvature in the primary roots of maize by affecting gravity induced-lateral auxin transport. Kim et al [6] suggested that an optimal concentration of ethylene might be required for the regulation of gravitropism in maize roots. Yuan et al [20] reported that cortical microtubule reoriented in wounding stem in pea from transverse to vertical orientation.…”
Section: Effects Of Oryzalin On the Gravitropic Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [7] suggested that ethylene may modify positive curvature in the primary roots of maize by affecting gravity induced-lateral auxin transport. Kim et al [6] suggested that an optimal concentration of ethylene might be required for the regulation of gravitropism in maize roots. Yuan et al [20] reported that cortical microtubule reoriented in wounding stem in pea from transverse to vertical orientation.…”
Section: Effects Of Oryzalin On the Gravitropic Responsementioning
confidence: 99%
“…Several factors regulate these two enzymes, especially auxin which stimulates the ethylene production through increasing the expression level of the ACS gene [21]. There are findings that ethylene regulates the root growth and gravitropism via alteration of auxin transport [6,13], and ethylene is required for root penetration in soil with auxin [14].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [15] suggested ethylene may modify positive curvature in the primary roots of maize by affecting gravity induced-lateral auxin transport. Kim et al [14] suggested that an optimal concentration of ethylene might be required for the regulation of gravitropism in maize roots. Based on these results, AA may affect the gravity induced-lateral IAA transport in maize root resulting in the inhibition of curvature by AA in the presence of IAA.…”
Section: Effectsmentioning
confidence: 99%
“…Several factors regulate these two enzymes, especially auxin which stimulates the ethylene production through increasing the expression level of the ACS gene [25]. There are findings that ethylene regulates the root growth and gravitropism via alteration of auxin transport [14,21], and ethylene is require for root penetration in soil with auxin [22].…”
Section: Introductionmentioning
confidence: 99%